Multi-level ?partnership? and Irish waste management: the politics of municipal incineration - Murray, Michael (Economic & Social Studies, 2006)
This article looks at the deployment of partnership-as-governance in the area of EU and Irish waste management and incineration policy. Looking at the specific case of plans to locate a municipal incinerator at Poolbeg in Dublin, the key argument offered is that institutional arrangements in this instance fail to address fundamental issues of power inequalities. As a result, concertation actually increases levels of citizen?s dissatisfaction and hostility, making community-based resistance against incineration all the more likely.
This paper was delivered at a conference ?Social Partnership: A New Kind of Governance?? funded by the Irish Research Council for the Humanities and Social Sciences, National Institute for Regional and Spatial Analysis and the Department of Sociology, NUI Maynooth, 14-15 September 2004.
Keywords: Partnership; Waste management; Local government; Ireland; Incineration